Capital struggles in security networks: A theoretical framework - Patriarca, Gabriel (Theoretical criminology, 2024)
The theme of networks is at the forefront of studies on plural policing, but concepts, typologies and theories focus more on collaborations than on conflicts. Based on a case study of the largest port complex in South America, the Brazilian port of Santos, this article proposes a theoretical framework for understanding capital struggles in security networks. It explores how struggles emerge from dynamics in which the network is at stake, such as membership and principles, or the forms of capital within it, which are claimed, contested, disputed or abdicated.